Mechanism of Propofol on Cardiac Function in Rats with Autoimmune Myocarditis via Regulation of HMGB1-RAGE Signaling - Jidong Lv; Lulu Zhang; Sijie Liu (Journal of Animal and Plant Sciences, 2026)
The experimental autoimmune myocarditis (EAM) remains an urgent issue to be addressed. The high mobility group box-1 (HMGB1)-receptor for advanced glycation endproducts (RAGE) signaling acts imperatively in pathogenesis of myocarditis. The aim of this study was to evaluate the potential mechanism of various doses of propofol in enhancing the cardiac function of EAM rats and its role in regulating HMGB1-RAGE signal transduction. Fifty rats were randomly and equally assigned to Control, EAM, low-dose propofol (LDP), medium-dose propofol (MDP), and high-dose propofol (HDP) groups. Control group received phosphate-buffered saline (PBS) injection (1 mL, oral gavage). EAM, LDP, MDP, and HDP groups were induced with EAM via porcine myocardial protein injection. Following model establishment, LDP, MDP, and HDP were delivered consecutively at 25, 50, and 100 mg/kg, respectively. Echocardiography assessed cardiac function parameters, namely left ventricular end-systolic diameter (LVESD, mm), LV end-diastolic diameter (LVEDD, mm), LV fractional shortening (LVFS), LV ejection fraction (LVEF). The serum cytokine levels were measured. Myocardial tissue was harvested for histopathological examination by Hematoxylin-eosin staining and scoring. The expression of MMP-3, MMP-9, TIMP-1, IL-1β, and inducible nitric oxide synthase (iNOS) in myocardial tissue was determined. Western blotting assessed the protein level of HMGB1 and RAGE in myocardial tissue. Compared with the Control group, EAM group exhibited significantly increased values of LVESD and LVEDD, higher myocardial inflammation scores, and elevated TNF-α, IFN-γ, TGF-β1, IL-17, MMP-3, MMP-9, IL-1β, iNOS mRNA expression, and HMGB1 and RAGE protein expression (P≤0.05). In contrast, LVFS and LVEF values, IL-4 and IL-10 levels, and TIMP-1 mRNA expression were significantly decreased (P≤0.05). However, compared with EAM group, MDP and HDP groups showed significantly reduced LVESD and LVEDD values, myocardial inflammation scores, and reduced TNF-α, IFN-γ, TGF-β1, IL-17, MMP-3, MMP-9, IL-1β, iNOS mRNA expression, and HMGB1 and RAGE protein expression (P≤0.05), while LVFS and LVEF values, IL-4 and IL-10 levels, and TIMP-1 mRNA expression weresignificantly increased (P≤0.05). Propofol improves cardiac function in EAM rats by modulating the balance between pro-inflammatory (Th1, Th17) and anti-inflammatory (Th2, Treg) responses and suppressing myocardial inflammation, an effect that may involve inhibition of the HMGB1-RAGE signaling pathway.
Keywords: Experimental autoimmune myocarditis; propofol; cardiac function; HMGB1-RAGE signaling